Perlindungan Hukum terhadap Keamanan Data Pribadi Pemegang Sertipikat Tanah Elektronik Dikaitkan dengan Kebocoran Data Berdasarkan Peraturan Menteri ATR/BPN No. 3 Tahun 2023 - Nicolas Roing Mbalur; Ketut Elly Sutrisni; Anak Agung Ayu Ngurah Sri Rahayu Gorda; Anak Agung Ayu Intan Puspadewi (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
The digitalization of land administration through electronic land certificates, as regulated under the ATR/BPN Ministerial Regulation No. 3 of 2023, introduces efficiency and transparency but simultaneously raises concerns regarding the protection of personal data. A critical issue lies in the lack of detailed regulatory provisions governing data breach handling and legal accountability. This study aims to examine the forms of legal protection for personal data within the electronic land certificate system and to analyze the legal responsibilities arising from potential data breaches. The research employs a normative juridical method using statutory and conceptual approaches, supported by primary and secondary legal materials. The findings indicate that legal protection is implemented through preventive mechanisms, including information system security and restricted access, as well as repressive measures based on the Personal Data Protection Law and Electronic Information and Transactions Law. However, the current regulation does not comprehensively address technical safeguards, sanctions, or specific procedures for data breach mitigation. This gap highlights the need for strengthening regulatory frameworks and improving cybersecurity measures to ensure more effective legal protection for electronic land certificate holders.